Randomized comparative trial of diode laser transscleral cyclophotocoagulation versus Ahmed glaucoma valve for neovascular glaucoma in Chinese – a pilot study - Choy BN (Dove Medical Press, 2018)
Bonnie Nga Kwan Choy, Jimmy Shiu Ming Lai, Jane Chun Chun Yeung, Jonathan Cheuk Hung Chan Department of Ophthalmology, University of Hong Kong, Hong Kong, People’s Republic of China Purpose: This is a pilot study to compare the effectiveness and safety of diode laser transscleral cyclophotocoagulation (TSCP) with the Ahmed glaucoma valve (AGV) in the management of neovascular glaucoma (NVG). Methods: Eyes with NVG and an IOP greater than 21 mmHg on maximal medications, without previous glaucoma surgery or cyclodestruction, were randomized for either TSCP or AGV implantation. These eyes were followed for at least 6 months and analyzed with respect to their visual outcome, IOP, number of glaucoma medications required, and related complications. Results: Twenty eyes (eight TSCP and 12 AGV) of 19 subjects with a follow-up duration of greater than 6 months were recruited. Mean follow-up duration was 28.5±17.9 and 31.0±15.4 months for the TSCP and AGV groups, respectively (P=0.80). IOP was successfully controlled in 86% of the eyes for both interventions. By including preservation or improvement of visual acuity as additional criteria for overall success, success decreased to 63% for TSCP and 42% for AGV, although the difference was not statistically significant (P=0.65). Eyes that had TSCP had fewer complications and required less subsequent procedures, compared to those that underwent AGV implantation. Conclusion: Both procedures were equally effective in controlling the IOP and reducing glaucoma medications in NVG. However, eyes with AGV implant tended to have higher rates of visual loss and complications, as well as requiring more postoperative procedures, than eyes that were treated with TSCP, although the difference was not statistically significant. Keywords: tube shunts, glaucoma drainage devices, glaucoma implants, cyclodiode, rubeotic glaucoma